The Differences of Students’ Self-Confidence Level in Full Day Class and Regular Class of Elementary School - Hidayati, Richma; Hidayah, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study aims to compare the students’ self-confidence between special classes (full day class) and regular classes. The method used is a quantitative study with a comparative study as a research design. The research subjects were 90 students, 30 students form special class and 60 students from regular class. The results of this study have provided an overview of the differences between special classes and regular classes affecting the level of student confidence where students in special classes have high self-confidence compared to students in regular classes. And it can be concluded that self-confidence is formed and develops through the learning process in one's interactions with the environment so that class differences make different levels of student confidence.